Awareness of e-cigarettes and correlation of use among high school students - Santistevan, Aysun, author; Makela, Carole J., advisor; Kennedy, Catherine, advisor; Nelson, Tracy, committee member; Timpson, William, committee member (Colorado State University. Libraries, 2016)
The purpose of this study was to assess awareness of e-cigarettes, to identify the factors associated with initial and continuing use of e-cigarettes, and to explore the reasons to use e-cigarettes among high school students. Three high schools in Colorado participated in the study. High school students (n = 251) who were enrolled in health classes were surveyed in the fall semester of 2015. The majority of students were sophomores (59%), followed by freshmen (28%), juniors (8%), and seniors (3%). A majority of students reported never using e-cigarettes (81%) and a few students reported using them in the past (14%), using them occasionally (4%), and a very few (.4%) using them everyday. Pearson's chi-squared tests were performed to examine correlations among variables since most of the variables were nominal and assumptions of the parametric data were violated. The awareness of e-cigarettes included seeing, hearing, or watching e-cigarette advertising, receiving information through social media, and sharing information about e-cigarettes with close friends. Findings revealed no significant correlations between seeing, hearing, or watching e-cigarette advertising and current use of e-cigarettes. Findings indicated a significant correlation between variables of receiving or sharing information about e-cigarettes and using e-cigarettes. Seventy-one percent of non-users, 21% of past users, and 7% of current users of e-cigarettes reported receiving information about e-cigarettes through social media. Sixty-percent of non-users, 29% of past users, and 11% of current users of e-cigarettes reported sharing information about e-cigarettes with close friends. The implication of findings showed that there has been exposure to e-cigarette advertising among high schoolers. The factors associated with initial and continuing use of e-cigarettes included teens' tobacco history, close friends', parents', and family members' e-cigarette and traditional cigarette use. Findings showed statistical significance between past, current, and future use of tobacco products and e-cigarette use in high schoolers. Fifty-one percent of students, who used tobacco in the past, reported past use of e-cigarettes, where 21% of students, who used tobacco in the past, reported current use of e-cigarettes. Findings suggested being a former or current smoker was correlated with having ever used e-cigarettes and past e-cigarette use. E-cigarettes may be used as a smoking cessation tool or alternative to other tobacco products. Further research is needed on the use of e-cigarettes among tobacco users. A few students (2%) considered e-cigarettes as a future use of tobacco products alone or with waterpipe tobacco and traditional cigarettes because of being seen as "fun", "cool", "harmless", and because "friends used them. " The associations between parents', family members', and close friends' use of cigarettes and e-cigarettes, and teens' current use of e-cigarettes were explored. Findings showed family members', and close friends' e-cigarette use was related to teens' e-cigarette use. Thirty-eight percent, who used e-cigarettes in the past or are currently using e-cigarettes, reported having at least one family member using e-cigarettes, and 45% who used e-cigarettes in the past or are currently using e-cigarettes reported close friends' e-cigarette use. Findings suggested that close friends' and family members' e-cigarette use may model behavior for teens and may provide a source for e-cigarette experimentation. Teens reported that "peer pressure" and "fitting into a social group" were some of the reasons that teens might initiate and continue use of e-cigarettes. Mann-Whitney U test was performed to explore gender differences in e-cigarette users' reasons to use e-cigarettes, and gender differences in non-e-cigarette users' reasons for the teens’ e-cigarette use. Reasons included curiosity, addiction, healthier than tobacco, cheaper than tobacco, quitting smoking, dealing with stress, losing weight, and socializing with friends. Females who used e-cigarettes in the past or are currently using e-cigarettes had a higher mean rank than males on the variables of dealing with stress (15.68; 8.05) and addiction (15.42; 7.55), respectively. Females, who never used e-cigarettes, had higher mean rank than males on variable of dealing with stress (119.50; 95.51) and losing weight (119.68; 97.25) as to teens' reasons to use e-cigarettes. E-cigarette messages and claims related to stress management and weight control might be leading young girls to experiment with or use e-cigarettes. It is crucial to restrict e-cigarette advertising and to educate teens on nicotine addiction and risk of respiratory diseases. Health educators should educate teens on the health effects of e-cigarettes and the health risk of dual or multiple use of tobacco products, and about using e-cigarettes as a cessation tool driven by perceptions of reduced harm and being an alternative to tobacco smoking.